A mixed-method evaluation of implementation determinants for chaplain intervention in a hospital setting. - Mascaro, Jennifer S.; Florian, Marianne P.; Brauer, Erin; Palmer, Patricia K.; Ash, Marcia J.; Shelton, Maureen; Palitsky, Roman; Kaplan, Deanna M.; Rana, Shaheen; Escoffery, Cam; Raison, Charles L.; Grant, George H. (Journal of Health Care Chaplaincy)
Healthcare chaplains address broad social and emotional dimensions of care within a pluralistic religious landscape. Although the development and evaluation of chaplaincy interventions has advanced the field, little research has investigated factors influencing the implementation of new chaplain interventions. In this mixed-method study, we examined attitudes about evidence-based interventions held by chaplain residents (n = 39) at the outset of an ACPE-accredited residency program in the southeast United States. We also used semi-structured interviews (n = 9) to examine residents' attitudes, beliefs, and decision-making processes after they trained in the delivery of a novel manualized intervention, Compassion-Centered Spiritual Health (CCSH). Most residents reported favorable attitudes toward manualized approaches prior to training. Interviews revealed complex decision-making processes and highlighted personal motivations and challenges to learning and implementing CCSH. Implementation science can reveal factors related to motivation, intention, and training that may be optimized to improve the implementation of healthcare chaplaincy interventions.